2019
DOI: 10.1002/ajp.22991
|View full text |Cite
|
Sign up to set email alerts
|

The changing ecology of primate parasites: Insights from wild‐captive comparisons

Abstract: Host movements, including migrations or range expansions, are known to influence parasite communities. Transitions to captivity-a rarely studied yet widespread human-driven host movement-can also change parasite communities, in some cases leading to pathogen spillover among wildlife species, or between wildlife and human hosts. We compared parasite species richness between wild and captive populations of 22 primate species, including macro-(helminths and arthropods) and microparasites (viruses, protozoa, bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Parasites passed through close contact may have fewer opportunities for cross‐species transmission, potentially limiting the distribution of hosts infected (Altizer et al, 2003; Thrall & Antonovics, 1997). Parasites with intermediate hosts are subject to additional habitat and geographic limits that may reduce opportunities for transmission across a wide host range (Herrera et al, 2019). While many parasites have life stages that can survive long periods in the environment, ultimately transmission may be limited by parasite survival (Park et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Parasites passed through close contact may have fewer opportunities for cross‐species transmission, potentially limiting the distribution of hosts infected (Altizer et al, 2003; Thrall & Antonovics, 1997). Parasites with intermediate hosts are subject to additional habitat and geographic limits that may reduce opportunities for transmission across a wide host range (Herrera et al, 2019). While many parasites have life stages that can survive long periods in the environment, ultimately transmission may be limited by parasite survival (Park et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in both free-ranging and captive NHPs are important, for instance, in the design of conservation strategies, reintroduction programs, and NHPs acquisition for research laboratories or zoos. Determining the composition of parasite communities in captive NHPs allows the identification of parasites of concern regarding the introduction of novel parasites to potentially susceptible wildlife populations during reintroduction programs, and also lead to a better understand parasite ecology, for instance, it has been observed that vector-borne parasites are more likely found in free-ranging NHPs, while parasites transmitted through either close and non-close contact, including the fecal-oral transmission, are more likely detected in captive NHPs [114].…”
Section: Discussionmentioning
confidence: 99%
“…Wild populations are inherently more immunologically variable (Viney & Riley, 2014), which is reflected in the large confidence intervals around our posterior mean estimates in bats. Many factors can influence wild-derived variation, but wild and captive animals can especially differ in pathogen exposure and stressors that can affect leukocyte composition (Davis et al, 2008;Herrera et al, 2019). Alternatively, the absence of allometry in our bat data (when analyzed alone in exercise 1), which are from wild populations, might be more likely to reflect true developmental and environmental pressures on these species.…”
Section: Are Bats Immunologically Different?mentioning
confidence: 97%